Power divider and balun filters with a single cross-coupled quadruplet - Lin, C.-H. (Institute of Electrical and Electronics Engineers Inc., 2019)
A filtering power divider and a filtering balun of fourth-order are synthesized with a single cross coupled quadruplet filter. The entire circuit uses only five resonators and both three-port circuits share four of the five resonators, leading to a compact circuit size and low insertion loss. In synthesis, given bandwidth, in-band return loss and transmission zeros, all coupling coefficients can be determined. For demonstration, a filtering divider and a filtering balun are designed at 2.4 GHz with a bandwidth of 5. Measured responses of the experimental circuits have good agreement with the simulated data, and this validates the synthesis. Â© 2019 IEEE.